Dynamic changes and clinical significance of serum tryptase levels in STEMI patients treated with primary PCI. (November 2014) - Chen, Shaomin; Mu, Di; Cui, Ming; Ren, Chuan; Zhang, Shu; Guo, Lijun; Gao, Wei
Abstract Objective: To investigate the dynamic changes in serum tryptase levels and their association with clinical data in patients with acute ST-elevation myocardial infarction (STEMI) treated with primary percutaneous coronary intervention (PCI). Methods: Serum tryptase levels were measured in 99 STEMI patients and 25 control subjects. Results: Tryptase levels were significantly increased at admission, and descended after primary PCI. Tryptase levels at 0.5, 2 and 6 h after PCI were negatively correlated with the percentage of ST-segment resolution (STR) as well as left ventricular ejection fraction (LVEF). Conclusions: High tryptase levels after PCI were associated with poor myocardial reperfusion and poor cardiac function.